Sugarcane mosaic virus reduced bacterial diversity and network complexity in the maize root endosphere - Wenbo Liu; Xin Cui; Xinhai Wang; Cheng Shen; Lingfei Ji; Min Zhang; Ming Hung Wong; Jin Zhang; Shengdao Shan (mSystems, 2023)
ABSTRACT Sugarcane mosaic virus (SCMV) causes mosaic disease in crops such as maize and sugarcane by its vector—an aphid—and is transmitted top-down into the root system. However, understanding of the effects of the aphid-borne virus on root-associated microbes after plant invasion remains limited. The current project investigated maize root-associated (rhizosphere and endosphere) bacterial communities, potential interspecies interaction, and assembly processes in response to SCMV invasion based on 16S rRNA gene amplicon sequencing. SCMV was detected in the roots 9 days after inoculation, and leaf mosaic and chlorosis appeared. The SCMV invasion markedly reduced the α-diversity of endosphere bacteria compared with uninoculated controls (Mock). The connectivity and complexity of the bacterial co-occurrence network in the root endosphere decreased after SCMV invasion, implying that the plant virus may alter root endophyte-microbial interactions. Moreover, a signature that deviates more from stochastic processes was observed in virus-infected plants. Unexpectedly, the rhizosphere bacterial communities were rarely affected by the viral invasion. This study lays the foundation for elucidating the fate of the microbial component of the plant holobiont following aphid-borne virus exposure. IMPORTANCE Biotic (e.g., soil-borne viruses) stress can alter root-associated bacterial communities, essential in maintaining host plant growth and health. However, the regulation of root-associated microorganisms by plant viruses from shoots is still largely unknown. Our results show that plant virus invasion leads to reduced and simpler inter-microbial communication in the maize endosphere. In addition, stochastic processes act on bacterial community assembly in both rhizosphere and endosphere, and bacterial communities in virus-invaded plant endosphere tend to shift toward deterministic processes. Our study highlights the negative effects of plant viruses on root endophytes from the microbial ecology perspective, which may be microbially mediated mechanisms of plant diseases.